2013
DOI: 10.1128/jvi.02688-12
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid 316 of Hemagglutinin and the Neuraminidase Stalk Length Influence Virulence of H9N2 Influenza Virus in Chickens and Mice

Abstract: e H9N2 influenza viruses with an A316S substitution in hemagglutinin (HA) and a shorter neuraminidase (NA) stalk have become predominant in China. The A316S was shown to increase HA cleavage efficiency when combined with short stalk NA, and the short stalk NA improved NA enzyme activity and release of virus from erythrocytes. Single mutations or combinations of these mutations strengthened the virulence of H9N2 virus in chickens and mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 30 publications
5
77
0
Order By: Relevance
“…In the quail study, we also found that the molecular changes due to mammalian adaptation did not affect the ability of the virus to replicate when both ferret-adapted surface genes were present. It has been reported that a functional balance between HA and NA activity is important for virus replication and transmission (Sun et al, 2013;Yen et al, 2011). An imbalance caused by an avian-origin HA and a mammalian-origin NA may account for the lack of proper replication and transmission…”
Section: Discussionmentioning
confidence: 99%
“…In the quail study, we also found that the molecular changes due to mammalian adaptation did not affect the ability of the virus to replicate when both ferret-adapted surface genes were present. It has been reported that a functional balance between HA and NA activity is important for virus replication and transmission (Sun et al, 2013;Yen et al, 2011). An imbalance caused by an avian-origin HA and a mammalian-origin NA may account for the lack of proper replication and transmission…”
Section: Discussionmentioning
confidence: 99%
“…Some mutations, however, are found to confer improved infection of both birds and mammals. For example, our previous study revealed that H9N2 viruses with an HA-A316S substitution and/or a shorter neuraminidase (NA) stalk are predominantly prevalent in avian strains and can increase virulence in chickens and mice (44). Thus, emerging or even established mutations in avian strains can exhibit increased viral infectivity in mammalian host species, which in turn could be different in avian species.…”
Section: Figmentioning
confidence: 99%
“…Two other substitutions (N313D and N496S) in the HA of an H9N2 AIV have been shown to enhance binding to both ␣2,3-linked sialic acid (SA␣2,3) and SA␣2,6 receptors (27). Some amino acid mutations such as A316S in HA and M147L, D253N, A588V, Q591K, E627K, and D701N in PB2 have been identified to play a critical role in enhancing replication of AIVs in mammals (23,(28)(29)(30)(31).…”
mentioning
confidence: 99%